EVIDENCIAS DE GLACIACION EN EL VALLE DEL GENERAL (COSTA RICA) DURANTE EL PLEISTOCENO TARDIO - Protti, Roberto (2011)
Glaciers and glacier morphology have been reported in Costa Rica only in the highest peaks of the TalamancaRange, over 3000 m. However, this paper reports the existence of glacier morphology at elevations of less than 1000 m in Valledel General, specifically along the western flank of the Talamanca Range.“U” shape valleys, frontal and lateral moraines, megalithic deposits with striation and glacial markings, polished rock planes,striae and groove cuts parallel to valleys are some of the evidence found in the San Rafael, San Pedro, and Peñas Blancas rivers.These features indicate the presence of glaciation during the Late Pleistocene in the Valle del General in Costa Rica.